SEIHR Model on Spread of COVID-19 and Its Simulation - Rois, Muhammad Abdurrahman; Tafrikan, Mohamad; Norasia, Yolanda; Anggriani, Indira; Ghani, Mohammad (Universitas Amikom Purwokerto, 2022)
The modified SEIR model of the COVID-19 spread is divided into five compartments: susceptible, exposed, infected, and recovered. Based on the results, two equilibrium points were obtained: the disease-free equilibrium point and the endemic equilibrium point. The existence of an equilibrium point depends on the value of the basic reproduction number R0, as well as on stability. The endemic equilibrium point exists if it is satisfied R0>1. Then, the disease-free equilibrium point is said to be locally asymptotic stable if R0<1, and the endemic equilibrium point is locally asymptotic stable if R0>1. Sensitivity analysis was performed to determine the most influential parameters in the spread of the virus. Finally, the numerical simulations determine the behavior of the model and support the results of the dynamic analysis.